THE ROLE OF COMMUNICATION OF COMMUNITY FIGURE IN AFFECTING THE VOTERS’ CHOICE IN THE ELECTION OF PEMATANGSIANTAR CITY, NORTH SUMATERA PROVINCE, 2016 - Aswan Jaya Jaya; Katimin Katimin Katimin (State Islamic University of North Sumatra Indonesia, 2017)
This study aims to explore the role of community leaders in influencing voter choice in Pematangsiantar City Head Election 2016. this research is a qualitative research with indication that every data in this research is expressed descriptively without using numbers and symbols. The research data is taken from interviews and direct case studies in the field by meeting community leaders and community members directly involved in the election of Pematang Siantar. The results showed that; 1). Community leaders who can influence voters' choice are those who have known the candidate partner for a long time and are close friends of the candidate pair. 2). Community leaders who can influence voters' choice are those who know only the Mayor or only the Vice Mayor. 3) Community leaders who can influence voters' choice are those who have worked with these candidates. as conclusion in this research can be explained that Pematangsiantar Pematangsiantar Pematangsiantar election is very influenced from elektabilitas Candidates against the People of Pematangsiantar City, so if the Candidates want to win this Pilkada then they must have a special closeness with community leaders there.Key Words; The Role of Communication, Community Figure, Voters’ Choice, Election